Breastfeeding in the first 6 months of life in obese children up to five years of age - Galvão, Dulce Maria Pereira Garcia (2020)
Galvão, DMPG. Sarmento, AF. Cunha, CA. & Santos, TA. Breastfeeding in the first 6 months of life in obese children up to five years of age. 15th International Breastfeeding and Lactation Symposium, organizado por Medela, decorreria a 26 e 27 de Março de 2020, em Lisboa. Evento cancelado a 27 de Fevereiro de 2020, devido à epidemia Covid-19.